Emergence of Predatory Publishing in Library and Information Science: Issues and Implications for Scholarship among Academic Librarians in Nigeria - Goodluck Ifijeh (Bilgi Dünyası, 2017)
Predatory publishing is an emerging but worrisome trend among academics including librarians in Nigeria. This paper examines crucial issues and implications of predatory publishing among Nigerian academic librarians. It outlines the characteristics of predatory publishers and journals and their subtle means of enticing unsuspecting authors. The paper discusses the intricate dimensions of predatory publishing and its effects on research and scholarship among librarians. It notes that predatory publishing has devastating effects on the future of research and scholarship. The paper concludes with strategies for intervention and a call on relevant authorities in Nigeria to take proactive steps to curb predatory publishing among faculties especially academic librarians.